Critical micro and secondary nutrient deficiency and supplementation influencing ginger production and quality in Eastern Ghat highland agroclimatic zone: Nutrient deficiency and supplementation on ginger production and quality - Panda, Aiswarya; Jena, Bandita; Nayak, Rabindra; Sial, Parsuram; Verma, Aditi; Das, Jyotirmayee; Mohanty, Shraddha; Behera, Sanjib (Journal of Spices and Aromatic Crops, 2025)
The Eastern Ghat Highland Agroclimatic Zone, covering major part of Koraput and Nabarangpur, has a warm, humid climate and hilly terrain at 900–1400 m MSL, favorable for spice crops like ginger. However, due to traditional farming methods by tribal communities, productivity remains low at 4.9 t/ha. Hence, an experiment was conducted in Pottangi, Koraput, to improve ginger yield by addressing micronutrient deficiencies (S, Zn, B) identified by the AICRP in local soils. The study tested ten treatments involving organic, inorganic, and foliar applications of secondary and micronutrients in light-textured, acidic sandy loam soil with low S, B, Zn but high Fe, Mn, and Cu. The ginger variety "Suprava" was cultivated, and foliar sprays were taken up at 60 and 90 days after planting. Significant improvements in plant growth parameters, such as height, tiller count, and leaf number, were observed with the nutrient treatments compared to recommended dose fertilizer (RDF). The highest rhizome yield (14.3 t /ha) was obtained with Zn + S, followed by IISR micronutrient foliar spray, while the lowest yield was from inorganic RDF. Organic treatments yielded better than inorganic, and combined or sole applications of secondary and micronutrients, particularly foliar sprays, enhanced yield and quality metrics like TSS, fibre, phenol, and protein contents. Regression analysis indicated a 98% influence of N, P, K, S, Zn, and B uptake on yield, underscoring the importance of supplementing deficient nutrients to improve yield, quality, and soil health.